Watkins Family Christmas Time - Watkins, Howard::::::::: (1989)
Frances Kamp, Robin Watkins holding her birthday teddy bear, Adam Watkins and Albert Watkins holding Christmas drink; Standing: Howard Watkins, Christine Watkins and Jerry Kamp; decorated Christmas tree with golden star on top in back